Effects of feeder adjustment on growth performance of growing and finishing pigs - A W Duttlinger; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
Two studies were conducted to determine the effects of feeder adjustment on growth performance of growing and finishing pigs. Both experiments were conducted at a commercial swine research facility in southwest Minnesota. In Exp. 1, a total of 1,170 barrows and gilts (PIC, initially 129.0 lb) were used in a 70-d study. Pigs were blocked by weight and randomly allotted to 1 of 5 treatments with 9 replications per treatment. The treatments were feeder settings of 1, 2, 3, 4, or 5, based on settings at the top of the STACO stainless steel dry feeders. Pigs were fed corn-soybean meal-based diets. From d 0 to 28, pigs fed from feeders with increasing feeder openings had increased (linear, P<0.04) ADG and ADFI. For d 28 to 70, increasing feeder setting did not affect (P>0.10) any growth performance traits. Overall (d 0 to 70), pigs fed from feeders with increasing feeder openings had increased (linear, P<0.03) ADFI. Changing feeder setting did not affect (P>0.18) ADG or F/G. In Exp. 2, a total of 1,250 barrows and gilts (PIC, initially 77.3 lb) were used in a 69-d study to determine the effect of feeder setting and diet type on growth performance of growing and finishing pigs. Pigs were blocked by weight and randomly allotted to 1 of 6 treatments with 8 replications per treatment. The treatments were arranged in a 3 × 2 factorial with main effects of STACO stainless steel dry feeder setting (1, 3, or 5) and diet type (corn-soybean meal- or by-product-based (15% DDGS and 5% bakery by-product). Overall (d 0 to 69), there were no feeder setting × diet type interactions (P>0.31) for growth performance. Diet type did not affect (P>0.75) growth performance. Increasing feeder openings increased ADG (qu-adratic, P<0.03) and ADFI (linear, P<0.01). Feeder setting tended to influence (quadratic, P>0.08) F/G with the best F/G at feeder set-ting of 3. In conclusion, feeding pigs from feeders with a more open feeder setting increased ADG and ADFI and tended to improve F/G at middle feeder settings compared with more closed feeder settings. With the dry feeders used in this study, feed should cover slightly more than half of the feed pan to avoid limiting pig performance.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; By-product; Dried distillers grains with solubles; Feeder adjustment; Finishing pigs